TOOL FOR ASSESSING THE LEVEL OF ENERGY SECURITY OF THE DECENTRALIZED POWER SUPPLY SYSTEM FOR ENTERPRISES IN CAMEROON - Novikova, Olga V; Nyemb, Bekoume S; Konnikov, Evgenii A (Naučno-tehničeskie vedomosti SPbGPU. Èkonomičeskie nauki (Online), 2020)
The development of the energy system in Cameroon is linked to the electricity supply and demand market. In recent years, the place of development of small and medium-size enterprises has began to have a significant impact on the balance of consumption. The choice of a specific scheme for the operation of a decentralized electricity supply system for enterprises in Cameroon should be based on objective criteria. Depending on the goals of the enterprise, this criterion can be the cost of implementing the project, discounted cash income, profitability growth with a predetermined forecast horizon, and many others. The choice of this criterion is associated with a multi – factor analysis of the goals of the enterprise and the specifics of its functioning, and the set of possible variations of this criterion can be conditionally designated as "Economic criteria". The article presents a tool for determining a comprehensive criterion for assessing the level of energy security of the decentralized power supply system for small and medium-sized businesses in Cameroon. The tasks solved in the framework of the study allow us to develop a system of economic management tools in energy systems. This tool can be widely used in the development of decentralized electricity supply for small and medium-sized businesses that are experiencing problems with the reliability of electricity supply. This will eventually create a more sustainable system for developing this sector of the economy.A characteristic feature of determining the key economic indicator is the dependence on the energy supply system. In one case it can only be revenue, in the second case it can be profitability and revenue, and in the third case profit, revenue and profitability. Perhaps a similar tool can be developed for the energy supply systems of enterprises in other countries.